Expected Enhancement of the Ship Monitoring and Control System - Tomas, Vinko; Vlahenić, Ivan; Šegulja, Ivica (Promet - Traffic&Transportation, 2012)
The intemational legislation places strict requirements onthe safety of navigation and the marine environment. One ofthe solutions to the problem is to enhance the ship navigationcontrol and maintenance with extensive use of informationtechnology, which has largely contributed to the growth of communicationtechnology. On the basis of an analysis of ship systemsautomation in the past, this paper deals with the developmentsand improvements to be expected ill the near future.Four generations of shipboard automation are presented, includingthe characteristics and requirements that the automationof ship control and monitming systems must fulflll in orderto be classified under a particular generation. Fields of furtherenhancement are considered as these will be decisive in increasingthe efficiency of business operations and ship safety.For the pwpose of supporting the claims above, actual trends inthe development of standards, equipment and systems havebeen analysed as well as their impact Oil the ship owner and thecrew.